X(logX-1) + C
logx^2=2 2logx=2 logx=1 10^1=x x=10
-logx=21.1 logx=-21.1 e^-21.1=x
y=logx y=10 logx= 10 10logx = 10log1 logx = log1 x = 1 //NajN
logx = 2 so x = 10logx = 102 = 100 ie x = 100.
logx^3logx^2log14 is 3logx2logxlog14 this equals 6 log14 (logx)^2 So for example, if y=6log14(logx)^2 the log x = square root of (y/6(log14))
The derivative of logx, assuming base 10, is 1/(xln10).
logx = 0.25 =1/4 4logx = 1 log x^4 = 1 x^4 = 10 x = 4th root of 10 =1.778
log base 10 x = logx
logx=12 x=10^12 x=1,000,000,000,000
You can't solve this since it isn't an equation.There is also an ambiguity (it's hard to write math on a typewriter keyboard) - are we talking about log(x3) or maybe logx(3)?Restate the question: Simplify log(x3)Answer: 3log(x)You could explain this by saying: log(x3) = log[(x)(x)(x)] = logx + logx + logx = 3logx. The general rule is log(xn) = nlogx.
(1/4)x^2(2logx-1) + c